Lipidomic analysis of Arabidopsis seed genetically engineered to contain DHA - Zhou, Xue-Rong; Callahan, Damien L.; Shrestha, Pushkar; Liu, Qing; Petrie, James R.; Singh, Surinder P. (Frontiers in Plant Science, 2014)
Metabolic engineering of omega-3 long-chain (≥C20) polyunsaturated fatty acids (ω3 LC-PUFA) in oilseeds has been one of the key metabolic engineering targets in recent years. By expressing a transgenic pathway for enhancing the synthesis of the ω3 LC-PUFA docosahexaenoic acid (DHA) from endogenous -linolenic acid (ALA), we obtained the production of fish oil-like proportions of DHA in Arabidopsis seed oil. Liquid chromatography-mass spectrometry (LC-MS) was used to characterize the triacylglycerol (TAG), diacylglycerol (DAG) and phospholipid (PL) lipid classes in the transgenic and wild type Arabidopsis seeds at both developing and mature stages. The analysis identified the appearance of several abundant DHA-containing phosphatidylcholine (PC), DAG and TAG molecular species in mature seeds. The relative abundances of PL, DAG and TAG species showed a preferred combination of LC-PUFA with ALA in the transgenic seeds, where LC-PUFA were esterified in positions usually occupied by 20:1ω9. Trace amounts of di-DHA PC and tri-DHA TAG were identified, and confirmed by high resolution MS/MS. Studying the lipidome in transgenic seeds provides insights into where DHA accumulated and composed with other fatty acids of neutral and phospholipids from the developing and mature seeds.